Epigrafika łacińska w farze poznańskiej. Inskrypcje w ołtarzach i kaplicach świętych jezuickich - Rosół, Rafał (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2019)
Rosół Rafał, Epigrafika łacińska w farze poznańskiej. Inskrypcje w ołtarzach i kaplicach świętych jezuickich (Latin Epigraphy in the Parish Church in Poznań. Inscriptions in the altars and chapels of the Jesuit Saints). The paper deals with some Latin inscriptions from the Parish Church in Poznań (the former Jesuit Church). The material under consideration is located in two altars and five chapels devoted to the Jesuit Saints. The author provides a critical edition of the texts, their Polish translations, as well as a commentary.